A stitch in time saves nine: Perceptions about colorectal cancer screening after a non-cancer colonoscopy result. Qualitative study. Issue 7 (July 2019) - Kirkegaard, Pia; Edwards, Adrian; Andersen, Berit
Highlights: Participation in cancer screening implies a risk for 'false alarm' for cancer. Patient-involvement can support trust in validity of a normal outcome. Trust can support motivation for subsequent screening after 'false alarm'. Motivation can build on perceived obligation to participate. Relationship between trust and obligation in screening needs further exploration. Abstract: Objectives: To explore perceptions of colorectal cancer (CRC) screening among participants who have experienced a 'false alarm' for CRC, and to explore perceptions about the relevance of screening for themselves or others. Methods: Semi-structured interviews with screening participants who had participated in the Danish CRC screening program and experienced a 'false alarm' for colorectal cancer. A thematic analysis was performed, based on an interpretive tradition of ethnography. Results: Perceptions about CRC screening after a non-cancer colonoscopy result were characterized by trust in the colonoscopy result showing no CRC, and satisfaction with the screening offer despite the risk for 'false alarm'. The patient-involving behavior of the healthcare professionals during the examination was for most participants a cornerstone for trusting the validity of the colonoscopy result showing no CRC. Strong notions about perceived obligation to participate in screening were common. Conclusions: Prominent themes were trust in the result, satisfaction with the procedure, and moral obligations to participate both for themselves and for others. Practice implications: Information to future invitees after a 'false alarm' experience could build on peoples' trust in the validity of a previous non-cancer result and should underscore the importance of subsequent screening even after a 'false alarm' for cancer.